Load balancing mechanism using Mobile agents - Cherbal, Sarra (Informatica, 2021)
Distributed systems need to perform load balancing on their hosts, so that the computation runs as quickly as possible. Research in this field has seen the emergence of mobile agents’ paradigm as a promising solution. In this present work, we use this paradigm to propose a load balancing approach that benefits from the advantages of agent mobility, more particularly, in the information gathering phase. In which, we aim to have an overall system vision while reducing network communication overhead, as well as other benefits such as fault tolerance and extensibility for large scale networks. Thus, the purpose of our contribution is to improve the distribution of loads in a balanced way to get loads as close as possible to the system average load. The experimental results show the efficiency of our approach on balancing the loads and in decreasing the response time.